Reprezentacija protestantov (»luterancev«) v zgodovinskih tekstih Ivana Tavčarja: Med zgodovino, fikcijo in ideologijo - Jensterle Doležal, Alenka (Slavia Centralis, 2020)
Representation of Protestants in historical texts by Ivan Tavčar The topic of the article isthe representation of reformersin the literary work of the Slovenian realist writer Ivan Tavčar (1851–1923). In our interpretation, we focus on the triptych of three literary works, written in the eighties, in which he describesthe period of recatolisation of the Slovene society. He depicted the images of reformistsin the shortstory Vita vitae meae (1883), in the story about Amandus as part of the longer "framed story" V Zali (In the Zala Valley, Ljubljanski zvon, 1884) and in the novel Grajski pisar (The Castle Scribe, 1889). Tavčar interweaved the texts with historical memory of the specific area of his youth: Poljanska Valley and the town Škofja Loka. The reformists as well as the catholic priests are presented with stereotypical features: they are passionate believers but also intolerant people without any sense of humanity and compassion for the Other. The narrator underlines the story of the romantic love between a man and a woman with different religious beliefs.